The Analysis of the Speed and Effectiveness of Resuscitation Actions in Patients with Cardiac Arrest in the Emergency Department: Analysis of the Speed and Effectiveness of Resuscitation Actions in Patients with Cardiac Arrest in the Emergency Department - Suryani (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Cardiac arrest is a medical emergency requiring rapid and effective resuscitation to improve patient survival. The speed of resuscitation has been linked to the success of return of spontaneous circulation (ROSC); however, delays are still common in many healthcare facilities. This study employed a quantitative method with a retrospective observational analytic design. Data were collected from medical records of cardiac arrest patients in the Emergency Department (ED) over the past year. Univariate analysis was conducted to describe patient characteristics, while bivariate analysis using the Chi-Square test and multivariate analysis using logistic regression were performed to examine the relationship between resuscitation speed and ROSC outcomes. Among the 60 patients analyzed, 58.3% were over 50 years old, and 66.7% were male. The Chi-Square test showed a significant relationship between resuscitation speed and ROSC success (p = 0.03). Logistic regression analysis indicated that patients who received resuscitation within less than 2 minutes had 2.5 times higher odds of achieving ROSC compared to those who received delayed resuscitation (p = 0.02). This study aligns with the American Heart Association guidelines and previous research, highlighting that the speed of resuscitation significantly influences patient recovery. Therefore, improving medical staff readiness and optimizing emergency response systems in EDs are crucial to enhancing the quality of cardiac arrest management.